The structure of human well-being related to ecosystem services in coastal areas: A comparison among the six North Pacific countries. (September 2018) - Hori, Juri; Makino, Mitsutaku
Abstract: The concept of human well-being and its relation to ecosystem services has been defined by the Millennium Ecosystem Assessment (MEA). To visualize the structure of human well-being related to ecosystem services in coastal areas, and to make an international comparison of these structures, this study investigated the satisfaction level of human well-being by using questionnaire survey, and the interactions among these components in the coastal areas of the six countries (Canada, China, Japan, Korea, Russia, and the US). The questionnaire items were selected according to the components of human well-being as defined by MEA. The analysis suggested a common hierarchical structure. Findings suggest the levels of satisfaction with 'Security' and 'Basic materials for a good life' functioned as the most fundamental variables among the five components of human well-being, while 'Health' and 'Good social relations' functioned as mediating variables of 'Freedom of choice and action'. The degree of interaction among the five components varied by country. In Canada and Russia, satisfaction with 'Security' had a more significant effect on 'Health' and 'Good social relations' than did 'Basic materials for a good life.' In the other countries, satisfaction with 'Basic materials for a good life' had a more significant effect on 'Health' and 'Good social relations' than did 'Security'. This study suggests that the structure of human well-being is dependent upon a range of natural and social factors. Knowledge of the differences which occurs across nations will be significant in establishing societal goals, and for societal engagement in marine conservation policy.